Quantum thermodynamics of an ?'-corrected Reissner-Nordstrom black hole - Pourhassan, Behnam; Sakalli, Izzet; Shi, Xiaoping; Faizal, Mir; Wani, Salman Sajad (Iop Publishing Ltd, 2023)
In this paper, we will go beyond equilibrium description to properly investigate the evaporation of a Reissner-Nordstro center dot m black hole. Thus, we will explicitly apply techniques of non-equilibrium quantum thermodynamics to this black hole. As the non-equilibrium effects would become important at the quantum scale, we will incorporate the quantum gravitational corrections by using an alpha'-corrected Reissner-Nordstro center dot m black hole. We will start by developing a novel alpha'-corrected first law. Then we will investigate the quantum gravitational corrections to the Parikh-Wilczek formalism, and introduce Kullback-Leibler divergence to quantify the effects of corrections. Furthermore, we will demonstrate that the non-thermal nature of radiation in the Parikh-Wilczek formalism can be directly related to the average quantum work done on the emitted particles using non-equilibrium quantum thermodynamics. This is because the average quantum work done is a unitary process in non-equilibrium quantum thermodynamics. We will use the Ramsey scheme for emitted particles to calculate this quantum work distribution for the emitted particles.
Keywords: Zero-Point Length; Holographic Principle; Entropy; Duality